Improvement in Glycemic Control in Mice of Different Age Groups - Gamage, Suhadinie; Peddibhotla, Swetha; Reddy, P. Hemachandra; Dhurandhar, Nikhil V.; Hegde, Vijay (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims and Methods The declining ability to control blood glucose with advancement of age is an important health risk factor and may lead to insulin resistance, type-2-diabetes and Alzheimer’s disease. Adenovirus 36(Ad36) improves glycemic control independent of insulin signaling(insulin sparing effect) as evidenced by cell, animal and observational human studies. This property of Ad36 may be useful in correcting aging-related glucose intolerance and related health conditions. Therefore, we determined the effect of Ad36 on glycemic control in older mice, to identify the age group that best responds to Ad36. Six, 12 or 20-month old C57Bl/6 mice on chow diet were each divided into weight-matched groups(mock-infected or Ad36-infected). Body weight was recorded weekly post infection (p.i.) and fasting glucose measured(week 0, 4, 8 and 20 p.i.). Blood glucose and serum insulin were measured during glucose tolerance test(week 0 and 16 p.i.). At week 20 p.i., animals were sacrificed, blood and tissues collected.Results Mice from all age groups showed improvement in glucose clearance post Ad36 infection, but a more profound effect was observed in 6-month old mice compared with mock-infected mice. Under fed conditions though there was no difference in blood glucose at 20 wk p.i., interestingly, Ad36 reduced serum insulin in age groups old mice, compared with control mice.Conclusions These findings suggest Ad36 infected animals improve glycemic control and clear post-prandial gluco00000se increase without increasing insulin secretion in an insulin sparing manner. These beneficial effects provide strong evidence for developing Ad36-based approaches as a novel tool to attenuate age associated glucose intolerance.
Keywords: glucose intolerance; adenovirus 36; insulin sparing; aging